Effects and Mechanisms of Resveratrol on Aging and Age-Related Diseases - Zhou, Dan-Dan; Luo, Min; Huang, Si-Yu; Saimaiti, Adila; Shang, Ao; Gan, Ren-You; Li, Hua-Bin (Oxidative medicine and cellular longevity, 2021)
The aging of population has become an issue of great concern because of its rapid increase. Aging is an important risk factor of many chronic diseases. Resveratrol could be found in many foods, such as grapes, red wine, peanuts, and blueberries. Many studies reported that resveratrol possessed various bioactivities, such as antioxidant, anti-inflammatory, cardiovascular protection, anticancer, antidiabetes mellitus, antiobesity, neuroprotection, and antiaging effects. The antiaging mechanisms of resveratrol were mainly ameliorating oxidative stress, relieving inflammatory reaction, improving mitochondrial function, and regulating apoptosis. Resveratrol could be an effective and safe compound for the prevention and treatment of aging and age-related diseases. In this review, we summarize the effects of resveratrol on aging, life extension, and several age-related diseases, with special attention paid to the mechanisms of antiaging action.